Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.nanolett.9b05179
|View full text |Cite
|
Sign up to set email alerts
|

Axion-Field-Enabled Nonreciprocal Thermal Radiation in Weyl Semimetals

Abstract: Objects around us constantly emit and absorb thermal radiation [1][2][3][4][5][6]. The emission and absorption processes are governed by two fundamental radiative properties: emissivity and absorptivity. For reciprocal systems, the emissivity and absorptivity are restricted to be equal by Kirchhoff's law of thermal radiation [1,2,7]. This restriction limits the degree of freedom to control thermal radiation and contributes to an intrinsic loss mechanism in photonic energy harvesting systems such as solar cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 205 publications
(106 citation statements)
references
References 38 publications
2
104
0
Order By: Relevance
“…In the context of photonic applications, Weyl semimetals have been proposed recently for generation of nonreciprocal surface plasmons and design of nonreciprocal thermal emitters. [ 40–42 ]…”
Section: Axion Electrodynamics Of Weyl Semimetalsmentioning
confidence: 99%
“…In the context of photonic applications, Weyl semimetals have been proposed recently for generation of nonreciprocal surface plasmons and design of nonreciprocal thermal emitters. [ 40–42 ]…”
Section: Axion Electrodynamics Of Weyl Semimetalsmentioning
confidence: 99%
“…The dimensionality of band-crossings is a criterion used to classify topological semimetals/metals. The most famous topological semimetals/metals with zero-dimensional band-crossings, i.e., zero-dimensional nodal points, are Dirac semimetals/metals (Chen et al, 2015(Chen et al, , 2020Bradlyn et al, 2017;Zhong et al, 2017;Jing and Heine, 2018;Liu et al, 2018b;Zhang et al, 2018b;Khoury et al, 2019;Wang et al, 2020f;Xu et al, 2020) and Weyl semimetals/metals (Peng et al, 2016;Lin et al, 2017;Fu et al, 2018;Zhang et al, 2018c;Zhou et al, 2019;Gupta et al, 2020;Jia et al, 2020;Liu et al, 2020;Meng L. et al, 2020;Zhao B. et al, 2020). We selected Weyl semimetals/metals as examples here because there exists a band-crossing of the valance band and conduction band at an isolated nodal point in the momentum space of these solids.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation in the area of nonreciprocal devices based on magnetic field bias is mainly focused on new materials such as WSs [ 127–130 ] ( Figure a,b), metamaterials and metasurfaces [ 131,132 ] (Figure 3c), magnetic 2D materials and heterostructures [ 133 ] (Figure 3d), new non‐linear ferroelectric materials, [ 134–136 ] and topological insulators [ 137,138 ] (Figure 3e,f). In this section, we briefly overview these important research areas with a focus on their nonreciprocal response.…”
Section: Advanced Nonreciprocal Materials: Wss Metamaterials Magnetmentioning
confidence: 99%
“…In the realm of light absorption and (thermal) emission, the reciprocity principle is expressed by Kirchhoff's law of thermal radiation that dictates that for reciprocal systems, the emissivity and absorptivity are restricted to be equal. [ 83,154 ] In recent work, however, it has been reported that nonreciprocal thermal emitters can be realized using topological magnetic WSs [ 128 ] that do not require strong magnetic fields (≈0.3–3 T) as in other existing approaches based on conventional magneto‐optical effects. [ 155,156 ] The authors predict Kirchhoff's law's violation in a broad angular and frequency range and its high temperature‐sensitivity.…”
Section: Advanced Nonreciprocal Materials: Wss Metamaterials Magnetmentioning
confidence: 99%